Commonly Isolated Pathogens from Postoperative Wounds and Antibiotic Susceptibility Testing аt a Tertiary Care Hospital in Stip, North Macedonia - Milka Zdravkovska; Tijana Serafimovska; Jasmina Tonic Ribarska; Marija Dimitrova; Svetlana Zivkova; Alen Georgijev; Iskra Sadikarijo; Trajan Balkanov; Marija Darkovska-Serafimovska (My University, 2020)
The increasing rates of hospital infections and bacterial resistance to commonly used antibiotics have created huge problem in the management of different infections. The objective of this study was to identify isolated pathogens from swab samples of postoperative woundstaken at a tertiary care hospital in Stip and to determine microbial susceptibility to antibiotics. Therefore, a total of 139 wound swab samples from two different departments (surgery and orthopedics) at a tertiary care hospital were processed using standard microbiological techniques. The colonies grown were identified based on colony morphology, Gram stains, and biochemical tests for accurate microbial identification. Antimicrobial susceptibility testing was performed by Kirby–Bauer disc diffusion technique. Among total 139 wound swab samples processed, from a total of 2344 operated patients, 100 samples (4,3%) were culture positive. The most common isolated gram-positive bacteria were Staphylococcus aureus (27 samples), among which 44% contained MRSA and Enterococcus (9 samples) among which 50% were found to have multidrug resistance to penicillin, macrolides, cephalosporines, clindamycin, folate synthesis inhibitors and quinolones. The most common isolated gram-negative bacteria were Escherichia coli (17 samples) and Pseudomonas aeruginosa (13 samples) among which 50% were found to have multidrug resistance to beta-lactam antibiotic, chloramphenicol, folate synthesis inhibitors and quinolones. The highest percentage of isolated pathogens was found in the samples obtained from the orthopaedic department. Gram-negative infections were predominant. Increased rate of MRSA resistance and multidrug resistance was noted.
Keywords: swab; postoperative wounds; antimicrobial susceptibility; bacterial resistance, multidrug resistance